Molecular characterization, evolutionary and phylogenetic analyses of rice ACT/BAT-type amino acid transporters. (October 2022) - Saha, Jayita; Gupta, Sumanti
Abstract: The Amino Acid-Polyamine-Organocation (APC) family transporters containing BAT/ACT (amino acid/choline transporters), PHS/LAT (polyamine H+-symporters) and CAT (cationic amino acid transporters) type transporters are ubiquitously reported in plants. ACT (containing BAT genes) which mediates bidirectional amino acid transport has been poorly characterized till date. In the present study, bioinformatics-based analytical studies have been performed to characterize the structural, functional, and evolutionary features of seven ACT/BAT transporters in the model crop Oryza sativa. Sequence homologies with allied transporters suggest that these seven transporter proteins can also have important roles in regulating amino acid transportation. Evolutionary and phylogenetic study of OsBATs proteins using different statistical models based on CDS, Protein, and UTR regions have brought forward some valuable information regarding their way and patterns of diversification over the time, possibly due to the influence of their prevailing growth conditions. Computational analyses based on promoter regions, exon-intron structural patterns, conserved motifs, secondary and tertiary structures and ligand binding sites with probable ligand names provided clues on their evolutionary structural diversification indicating changes in their functional specification probably needed to combat with the changing environment. Graphical Abstract: ga1 Highlight: Bioinformatics-based analytical studies have been performed to characterize the structural, functional, and evolutionary features of seven ACT/BAT transporters in the model crop Oryza sativa . Evolutionary and phylogenetic study of OsBATs proteins using different statistical models based on CDS, Protein, and UTR regions have brought forward some valuable information regarding their way and patterns of diversification over the time, possibly due to the influence of their prevailing growth conditions. Computational analyses based on promoter regions, exon-intron structural patterns, conserved motifs, secondary and tertiary structures and ligand binding sites with probable ligand names provided clues on their evolutionary structural diversification indicating changes in their functional specification probably needed to combat with the changing environment.